New Fixed Point Theorem for Expansive Maps on a Two – Metric Space - Sami Abdullah Abed (ASJ - Academic Science Journal, 2024)
In this paper new theorems a bout fixed point are given for applications in 2- metric space. The common fixed points of two operators exhibit a shared periodicity in their occurrences. The theorem demonstrates that, certain conditions, there exists a specific pattern or sequence of operators where the fixed points exhibit a common periodicity.